Respiratory outcomes among refinery workers exposed to inspirable alumina dust: A longitudinal study in Western Australia. Issue 12 (17th September 2020) - Del Monaco, Anthony; Gwini, Stella M.; Kelly, Sarah; de Klerk, Nicholas; Benke, Geza; Dennekamp, Martine; Fritschi, Lin; Dimitriadis, Christina; William (Bill) Musk, Arthur; Abramson, Michael J.; Sim, Malcolm R.
Abstract: Background: Information is scarce about the occupational health effects of exposure to alumina dust. This study examines the respiratory effects of inspirable alumina dust exposure in alumina refineries. Methods: An inception cohort study at three alumina refineries in Western Australia recruited 416 participants (351 males, 65 females) between 1995 and 2000 who were followed up annually until 2008 or until exit from study. At each health interview a respiratory questionnaire and lung function test was undertaken, measuring forced expiratory volume in one second (FEV1 ) and forced vital capacity (FVC). Participants provided job histories which were combined with air monitoring data to calculate cumulative exposure to inspirable alumina dust (mg/m 3 ‐years). Generalized estimating equations with Poisson distribution and mixed effects models were used to examine the effects of alumina exposure. Results: The number of exposed participants was relatively small ( n = 82, 19.7%). There was no association between alumina dust exposure and prevalence of cough, wheeze or rhinitis. No associations were found between measures of lung function and tertiles of alumina exposure in the first two follow‐ups, or the whole follow‐up period, though there was a suggestive dose‐response trend across exposed groups for decline in absolute FEV1 ( p for trend = .06). For mean annual change in FEV1 and FVC based on the first three follow‐ups it was not possible to rule out an effect above a threshold level of exposure. Conclusion: There is no evidence of an association between exposure to alumina and the reporting of respiratory symptoms but some evidence for an effect on lung function.